Rapid, wide-field, high quality laser speckle angiography for retinal and choroidal vessels. (20th April 2021) - Feng, Ximeng; Zou, Da; Hu, Yicheng; Huang, Zhiyu; Gu, Zheng; Zhou, Cuanqing; Liu, Gangjun; Ren, Qiushi; Lu, Yanye
Abstract: Laser speckle contrast imaging has been widely used for quantifying blood perfusion. In this letter, we propose a rapid, wide-field laser speckle angiography technique for noninvasive imaging of retinal and choroidal vessels. The field of view (FOV) reaches ∼50 ∘ while the acquisition time was less than 1 s. Larger FOV (∼90 ∘ ) can be further improved by mosaicking. The results were comparatively studied with optical coherence tomography angiography and fundus fluorescence angiography. The low-cost technology can obtain wide-field fundus vascular and perfusion images less than 1 s. This technology is more suitable for optic disc and choroidal vasculature imaging. In addition, blood flow dynamic information such as pulsation can be provided by this technique.